The Inculcation of Loving Reading Quran Values at the Reading Quran Institution, Home, and Community - Wirdanengsih Wirdanengsih; Dasim Budimansyah; Sofyan Sauri (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2017)
The purpose of this study was intended to describe the value of loving reading Al-Quran that was implemented by three education centers; Reading Quran Insitution Awaliyah, Family and Community Education for children between 9-12 years old in Nagari Balai Gurah. Also, this research was to discover how is the implementation of loving reading Al-Quran values and who are involved in it. The result indicated that the implementation of the values of loving reading Al-Quran basically used surveillance approaches and guidance from the tutors, parents, and community in Reading Al-Quran. The socialization pattern that was used in implementing the value of love reading Al-Quran at Reading Quran Institution and family tended to use flexible patterns between authoritative and permissive patterns. Parties who involved in implementing the value of loving reading Al-Quran were the Awaliyah Institution, teacher and management, and family consisting of fathers, mothers, siblings, and grandparents. The uniqueness came from the roles of cultural social values in the community stating children who did not learn and love Al-Quran will be an embarrassment to the family. Moreover, the ceremony of Khatam Quran became the strong factor for children in implementing loving reading Al-Quran, due to this ceremony there was a process of social acknowledgement to the children who love reading Al-Quran.